2022
DOI: 10.3390/genes13081491
|View full text |Cite
|
Sign up to set email alerts
|

Association Analysis for Some Biochemical Traits in Wild Relatives of Wheat under Drought Stress Conditions

Abstract: In the present study, we estimated genetic diversity and population structure in 186 accessions of Triticum and Aegilops species using 24 simple sequence repeat markers (SSR). Furthermore, an association analysis was performed for antioxidant activities, including guaiacol peroxidase (GPX), ascorbate peroxidase (APX), peroxidase (POX), catalase (CAT), and dry matter (DM) under two control and drought stress conditions. Our findings showed that drought treatment significantly decreased DM, whereas activities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 63 publications
1
1
0
Order By: Relevance
“…tauschii accessions showed higher genetic variation parameters relative to T. aestivum accessions ( Table 3 ). Indeed, this result is in agreement with other studies, where Naghavi et al [ 33 , 34 ] and Pour-Aboughadareh et al [ 35 ] reported considerably higher levels of genetic variation among Ae. tauschii than T. aestivum accessions.…”
Section: Discussionsupporting
confidence: 93%
“…tauschii accessions showed higher genetic variation parameters relative to T. aestivum accessions ( Table 3 ). Indeed, this result is in agreement with other studies, where Naghavi et al [ 33 , 34 ] and Pour-Aboughadareh et al [ 35 ] reported considerably higher levels of genetic variation among Ae. tauschii than T. aestivum accessions.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, there has been an increased interest in studying physio-biochemical responses and gene expression profiling associated with antioxidants in neglected Aegilops species under salt stress conditions [16,27,28,47,48]. Studying these species can provide valuable insights into the mechanisms by which plants adapt to extreme environments, and can serve as a basis for developing breeding strategies to increase salt tolerance in crops [15,17,33,34,36]. This study comparatively revealed the response of three neglected Aegilops species (Ae.…”
Section: Discussionmentioning
confidence: 93%
“…Tocopherols, carotenoids, ascorbate acid (AsA), and glutathions (GSH) are grouped in the non-enzymatic system. Both antioxidant systems have critical roles in improving the tolerance of plants coping with various environmental stresses, and they can also be used as useful biomarkers for the selection of tolerant plant materials [14][15][16][17][18][19]. Hence, the regulation of antioxidant-related genes could increase plant tolerance to salinity stress [20].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [26] found four continuous markers of EGA resistance and tolerance in different growth stages of wheat when using SSR markers for association analysis, which provided a basis for molecular assisted breeding of wheat. Pour et al [27] analyzed the genetic diversity and association of 186 wheat and wild relative germplasms using 24 SSR markers and found that there were eight significant markers associated with APX, CAT, and DM under control conditions and nine significant markers associated with APX, GPX, POX, DM, and STI under drought stress. Breseghello et al [28] performed association mapping of 95 winter wheat varieties using 88 SSR markers, detected significant markers associated with grain size on three chromosomes, and identified alleles that might be useful for genome selection.…”
Section: Introductionmentioning
confidence: 99%